An analysis of existing groundwater management and policy matters in Industrial areas : A case study from Rathupaswala - Ranmadugala, S.B.H.; Kodithuwakku, K.A.W. (University of Colombo, 2015)
Due to non availability or inadequacy of surface water resources, groundwater has become more popular in water supplies in past few decades in Sri Lanka. At the same time, pollution of groundwater is one of the major constraints for this valuable resource. Impacts of industrial, agriculture and urban activities have been identified as the major sources for contamination of groundwater(Panabokke and Perera 2005). Among these, industrial activities play a significant role in ground water pollution in the recent past in Sri Lanka. In addition to pollution control development and implementation of ground water policies and reliable ground water management is essential for an effective ground water management in the country. This in turn significantly affected the implementation of a formally approved water policy for the country (Gunatilake and Gopalakrishnan 2002, Samad 2005). A National policy must be flexible and should be able to accommodate the diverse groundwater contamination problems that come across by varying site conditions(Rail 1989). Bacon and Oleckno (1985) highlighted the importance of establishing a groundwater protection program at national level, the importance of revealing the contamination sources, making an inventory and understanding the hydrogeology of respective areas.
Keywords: An analysis of existing groundwater management and policy matters in Industrial areas : A case study from Rathupaswala